2018
DOI: 10.1080/09503153.2018.1476477
|View full text |Cite
|
Sign up to set email alerts
|

Using Visual Methodology: Social Work Student’s Perceptions of Practice and the Impact on Practice Educators

Abstract: is a senior lecturer in social work. She is a registered social worker qualifying in 1995 and worked in various adult services prior to working independently as a practice educator and visiting lecturer. Bridget joined the UoC social work department two years ago. She retains a strong interest in developing practice learning and still undertakes practice educating. Bridget also is interested in promoting learning from service users and carers and the continuing professional development of social workers. Siobh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Other studies identified in initial scoping reviews of the topic utilised similar photo-elicitation methods but with a sample of university or college students from other subjects; all indicated in their findings that photography based research methods were more effective than traditional methods, such as observation or interviews at engaging student participation ( Anderson, 2016 ; Patka et al, 2017 ). While these studies did demonstrate effectively the success of visual methods, their claims that this method was more successful than traditional research methods ( Anderson, 2016 ; Bailey-McHale et al, 2019 ; Morley et al, 2017 ) appear to be largely unproven as none of the researchers cite any comparable studies in order to properly critique and contrast the methods and their effectiveness in engaging students. This claim, while possible given the anecdotal evidence from respective researchers, participants and my own research experiences would benefit from further study with appropriate comparative assessment methods.…”
Section: Existing Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Other studies identified in initial scoping reviews of the topic utilised similar photo-elicitation methods but with a sample of university or college students from other subjects; all indicated in their findings that photography based research methods were more effective than traditional methods, such as observation or interviews at engaging student participation ( Anderson, 2016 ; Patka et al, 2017 ). While these studies did demonstrate effectively the success of visual methods, their claims that this method was more successful than traditional research methods ( Anderson, 2016 ; Bailey-McHale et al, 2019 ; Morley et al, 2017 ) appear to be largely unproven as none of the researchers cite any comparable studies in order to properly critique and contrast the methods and their effectiveness in engaging students. This claim, while possible given the anecdotal evidence from respective researchers, participants and my own research experiences would benefit from further study with appropriate comparative assessment methods.…”
Section: Existing Literaturementioning
confidence: 99%
“…Bowers (2017) used Photovoice as a method of engaging social work students in critical reflection and found that using Photovoice allowed students to reflexively analyse and develop their professional identities and consider what that meant for their practice. In addition to Bowers (2017) study, I identified 7 other studies that utilised Photovoice with social work students with various research aims (Bailey-McHale et al, 2019; Bowers, 2017; Bromfield and Capous-Desyllas, 2017; Byrne et al, 2009; Chonody, 2018; Morley et al, 2017; Phillips and Bellinger, 2010; Walsh et al, 2015). Other studies identified in initial scoping reviews of the topic utilised similar photo-elicitation methods but with a sample of university or college students from other subjects; all indicated in their findings that photography based research methods were more effective than traditional methods, such as observation or interviews at engaging student participation (Anderson, 2016; Patka et al, 2017).…”
Section: Existing Literaturementioning
confidence: 99%
See 1 more Smart Citation